2017
DOI: 10.21608/smj.2017.34969
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between Ketamine and dexamethasone added to bupivacaine in ultrasound guided infra clavicular brachial plexus block for upper limb surgeries

Abstract: Background the aim of this study is to compare between ketamine and dexamethasone when added to bupivacaine in ultrasound guided infraclavicular brachial plexus block for upper limb surgeries. Methods: The patients were randomly allocated to two groups, 25 patients each: Group K (ketamine group) Patient received 30 ml of 0.375% bupivacaine plus 0.5 mg/kg ketamine in 2 ml saline Group D (dexamethasone group) Patient received 30 ml of 0.375 bupivacaine plus 8 mg dexamethasone in 2 ml. Results: Onset time of sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It was previously demonstrated that ketamine has a local anesthetic-like action through interaction with the rat myocyte's sodium channel. Ketamine also blocks the N-methyl-D-aspartate receptors incorporated in the pain pathway [8][9][10][11][12][13][14]. The aforementioned effects could explain the trial of ketamine as an adjuvant during fascial plane blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously demonstrated that ketamine has a local anesthetic-like action through interaction with the rat myocyte's sodium channel. Ketamine also blocks the N-methyl-D-aspartate receptors incorporated in the pain pathway [8][9][10][11][12][13][14]. The aforementioned effects could explain the trial of ketamine as an adjuvant during fascial plane blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, an intravenous anesthetic, has been used as an adjuvant to LA during combined sciatic-femoral nerve block [8], axillary block [9], infraclavicular brachial plexus block [10], thoracic paravertebral block [11], Modified Pectoral Block [12], interscalene brachial plexus block [13], and femoral nerve block [14]. However, the ketamine results were controversial, varying from enhancing the LA's onset and prolonged duration to not improving the onset or duration of the sensory block.…”
Section: Introductionmentioning
confidence: 99%